Increased resistance to a generalist herbivore in a salinity-stressed non-halophytic plant. (18th August 2015) - Renault, Sylvie; Wolfe, Scott; Markham, John; Avila-Sakar, Germán
Abstract : During their life, plants face multiple stresses. However, studies on one stress factor have typically neglected possible interactions with other factors. We demonstrated that salt stress in Indian mustard (a plant species not adapted to salinity) lessens the effect of herbivory on plant mass, and increases the plants' constitutive resistance to herbivores. Changes in the plants associated with increased salt that help to explain the mitigation of herbivore effects include decreased protein and macronutrient content. Plants exposed to herbivore damage were also less negatively affected by salt exposure, possibly due to their ability to maintain higher levels of transpiration. Abstract: Plants often grow under the combined stress of several factors. Salinity and herbivory, separately, can severely hinder plant growth and reproduction, but the combined effects of both factors are still not clearly understood. Salinity is known to reduce plant tissue nitrogen content and growth rates. Since herbivores prefer tissues with high N content, and biochemical pathways leading to resistance are commonly elicited by salt-stress, we hypothesized that plants growing in saline conditions would have enhanced resistance against herbivores. The non-halophyte, Brassica juncea, and the generalist herbivore Trichoplusia ni were used to test the prediction that plants subjected to salinity stress would be both more resistant and more tolerant to herbivory than those growing without salt stress. Plants were grown under different NaCl levels, and either exposed to herbivores and followed by removal of half of their leaves, or left intact. Plants were left to grow and reproduce until senescence. Tissue quality was assessed, seeds were counted and biomass of different organs measured. Plants exposed to salinity grew less, had reduced tissue nitrogen, protein and chlorophyll content, although proline levels increased. Specific leaf area, leaf water content, transpiration and root:shoot ratio remained unaffected. Plants growing under saline condition had greater constitutive resistance than unstressed plants. However, induced resistance and tolerance were not affected by salinity. These results support the hypothesis that plants growing under salt-stress are better defended against herbivores, although in B. juncea this may be mostly through resistance, and less through tolerance.